Hukum Responsif: Hukum sebagai Institusi Sosial Melayani Kebutuhan Sosial dalam Masa Transisi - Sulaiman Sulaiman; Muhammad Nasir (Prodi Ilmu Hukum, Universitas Teuku Umar, 2023)
The purpose of this paper is to analyze more deeply responsive legal concepts developed by Nonet and Selznick, the differences between the types of responsive law to the type of autonomous laws and law as a social institutions that serve social needs in transition. The results obtained, responsive law types have prominent features, namely: a. The shift in emphasis from rules to principles and objectives; b. The importance of the character of populist either as a law purpose and how to achieve it. The main characteristics of an autonomous law types are: a. The emphasis on the rule of law as a major effort to oversee the formal and informal power. b. Free trial. c. Separation of law from politics. d. The Court can not guarantee but may seek the law is just. The law is a social institution, viewed more than a mere regulatory system and in transition meet social needs.